Ural, Russische Föderation. Feuchtbodenarchäologie und Dendrochronologie im Ural – Ein neues Aufgabenfeld für die Eurasien-Abteilung. Die Arbeiten der Jahre 2017 und 2018 - Reinhold, Sabine (e-Forschungsberichte des DAI, 2019)
The piedmonts of the Ural mountain range harbor a nearly unknown area of wetland sites with spectacular finds. The Big Shigir-Idol, for instance, is the oldest known wooden sculpture and dated to c. 9600 BC. Theses wetland sites are located in lakes and peat-bogs east of the Ural. Since 2017, the Eurasia-Department has taken part in the excavation of such a wetland site in the Gorbunovo peat-bog near the city of Nishniy Tagil. The excavations in cooperation with the Academy Institute of Ekaterinburg revealed large, complex wooden constructions, which can be dated by radiocarbon and dendrochronological investigation to the 4th and 3rd millennium BC.